Asymmetric Laser Field Interaction with MXene Coated on the Side Surface of Optical Fibers for Ultrafast Nonlinear Switches - SIAM, MD. UDDIN; Debnath, Pulak C.; Kim, Hyerim; Moon, Hyowon; Koo, Chong Min; Song, Yong-Won (American Chemical Society, 2024)
In recent years, there has been significant interest in researching ultrafast nonlinear optical phenomena involving light-matter interactions in two-dimensional (2D) materials, owing to their potential applications in optics and photonics. MXene, a recently developed 2D material, has garnered considerable attention due to its graphene-like properties and highly tunable electronic/optical characteristics. Herein, we demonstrate ultrafast all-optical switches based on four-wave-mixing (FWM) utilizing the nonlinear optical property of MXene Ti3C2Tx. In order to realize the device, we deposited multilayered Ti3C2Tx in the form of a supernatant solution onto the polished surface of a side-polished optical fiber, enabling the interaction of Ti3C2Tx with the asymmetric evanescent field of the incident input. We systematically characterized the nonlinear optical responses derived from the Ti3C2Tx layers. The fabricated device exhibits notable performance metrics, an enhancement of the extinction ratio, and a conversion efficiency of the newly generated signal, displaying 5.3 and 5.2 dB, respectively. Additionally, the device operates at high modulation frequencies, reaching up to 20 GHz, and demonstrates high-resolution detuning with channel distances of up to 15 nm. Our findings highlight the potential of MXene-based materials for ultrafast optical data management systems.